IMPROVING STUDENTS LEARNING OUTCOMES IN SOCIAL SCIENCE LEARNING THROUGH THE SNOWBALL THROWING METHOD - Lilis Iswatul Jannah; Agung Setyawan (Citra Dharma Cindekia, 2022)
This research started from the problem of teachers who continuously used the lecture method, causing student learning outcomes, especially for low social studies content. Therefore, this classroom action research was conducted to improve student learning outcomes by applying the Snowball Throwing method. This research was conducted in 2 cycles, with the subject of 13 students of SDS Muhammadiyah 1 Pataan. The data collection method in this study used the methods of observation, interviews, tests, and documentation. With the data source of class IV homeroom and students. As for the results obtained, the average score of the class at the time of the pre-cycle was 59, the first cycle obtained an average grade of 72.70 in the second cycle obtained an average of 81.54. There is also the percentage of mastery learning in the pre-cycle got a score of 31% (not classical completion), cycle 1 is 58.85% (Classical Completed) and cycle II is 93.30% (Classical Completed). By using the KKM of 70. From the results of this study the use of the Snowball Throwing method can improve student learning outcomes in social studies learning, so that later this research can be useful for educators